Electromagnetic wave attenuation property of mesoporous xylose coated maghemite - Yang, Cenlin (2015)
Xylose coated mesoporous maghemite (γ-Fe2O3) was designed to achieve high performance electromagnetic wave attenuation. The xylose coating helps unity the value of the permittivity and permeability significantly and hence a better impedance value. Moreover, a silica coating was removed between γ-Fe2O3 nano-rods and xylose coating, but the xylose coating helped to maintain rod-like shape of the particles and ensured a mesoporous structure. The synthetic process consists of five steps. -FeOOH was first produced as starting material by hydrolysis synthesis. Then, the FeOOH nano-rods were coated with silica. Subsequently amino-functionalization was conducted on the silica coating in order for xylose to be coated onto the surface. Xylose was coated onto the particle surface by using the hydrothermal carbonization method. Afterwards thermal treatment was conducted to transfer FeOOH into γ-Fe2O3. Finally SiO2 was removed by NaOH solution. The reflection loss result for γ-Fe2O3@HTC-xylose shows that it is able to give an EM wave attenuation property with -26.8094 dB at 17 GHz for 6 mm thickness. Thickness range from 5.5–6 mm are able to hit more than 99% wave absorption by exceeding RL of −20 dB between 15 GHz to 18 GHz. The silicon resin composites containing γ-Fe2O3@HTC-xylose gives theoretical result that indicates it should be a possible promising strong EM wave attenuation material and meanwhile being light weighted.